Conflict Approaches of Effective Project Manager in the Upstream Sector of Indonesian Oil & Gas Industry - Cahyono, Adhi; Hartijasti, Yanki (UI Scholars Hub, 2012)
Conflict can be functional or dysfunctional to the organization’s performance. This study focused on the relationship between conflict approaches implemented by the project manager based on project team member’s perception on the effectiveness of the project manager in managing project’s conflict. Questionnaires were modified from Barker et al. (1988) to measure conflict management approaches and outcomes of managing project conflict. Data were gathered from 57 respondents who worked in the Engineering, Procurement, and Construction (EPC) contractors serving the upstream sector of the Oil and Gas industry in Indonesia. By using Pearson correlation, result of this study indicated that project managers were perceived to be effective in managing project conflict when implementing cooperative and confi rmative approaches, but ineffective when combining competitive and avoidance approaches. Further research should investigate correlation between cultural dimensions with conflict approaches and outcomes of managing conflict.